Tanggapan Anak terhadap Pembinaan Kedisiplinan di Panti Asuhan Bina Remaja Budi Utama Lubuk Alung - Anisah Nur; Vevi Sunarti (RC-INSTITUT, 2020)
This research is motivated by the high participation of foster children in applying the discipline applied by caregivers at Budi Utama Orphanage, Lubuk Alung. This is caused by the application of good disciplinary guidance by caregivers. This study aims to describe the child's response to disciplinary development at the Budi Utama Orphanage, seen from the aspects of loyalty, regularity, commitment, and consistency. The approach used in this study uses quantitative descriptive techniques. The population of this research is adolescents who are in the Budi Utama Lubuk Alung Orphanage and the sample is taken using a stratified random sampling technique. Data collection techniques using a questionnaire with data collection tools using a questionnaire and data analyzed using percentage techniques. The results of this study indicate that based on aspects of overall disciplinary guidance looks good. This is evidenced by the many foster children who provide alternative answers always and often. Based on the results of this study, it is expected that caregivers and parents can maintain and improve discipline guidance for children so that children can grow and develop in accordance with applicable norms.